The Class of 2019: Academic Employment Prospects for Counselor Education Doctoral Graduates - Christopher Lawrence; Gregory Hatchett (Teaching and Supervision in Counseling, 2024)
The purpose of this investigation was to estimate the percentage of counselor education doctoral (CED) program graduates who attained faculty positions within two years of graduation and to compare the number of these graduates to the number of advertised faculty positions during this same timeframe. To do so, we used archival, publicly available data for graduates of CACREP-accredited CED programs during the 2018-2019 academic cycle (N = 314). Approximately two-fifths of these graduates had faculty positions. Graduation from a public university increased the odds of having any faculty post, whereas graduation from a public university and the Carnegie Classification of the degree granting institution increased the odds of having an assistant professor position in an accredited counseling program. Overall, there were 1.5 graduates for every faculty position, a ratio that varied based on the position’s nature and geographical location. Implications for faculty career development in counselor education are presented.
Keywords: counselor education; faculty positions; employment; doctoral study; CACREP